IFPRI IMPACT webtool - Robinson, Sherman; Mason-D’Croz, Daniel; Islam, Shahnila; Sulser, Timothy B.; Robertson, Richard D.; Zhu, Tingju; Gueneau, Arthur; Pitois, Gauthier; Rosegrant, Mark W. (International Food Policy Research Institute, 2015)
The International Model for Policy Analysis of Agricultural Commodities and Trade (IMPACT) web tool is a fully interactive online tool designed to highlight and make public the results of simulations performed with the IMPACT model and carried out through various projects. The tool offers: 1)user-friendly access to scenario details and results data coming from IMPACT simulation runs; 2) user-friendly access to the input data that drive the IMPACT simulations 3) Downloadable publications describing IMPACT analyses addressing policy issues relevant to global agricultural markets, including issues of climate change, technology change, food security, and resource management.